EFFECT OF EMOTIONAL INTELLIGENCE ON EMPLOYEE PERFORMANCE: A LITERATURE REVIEW - Nur Allysha binti Mohamad Pharani; Adhwa Adlin binti Mohd Shahar; Nurin Jazlina binti Mohd Tahir; Nur Farisha Irwayu binti Yauza; Wan Aisyah Amni binti Wan Mohamad Saferdin (International Journal of Accounting, Finance and Business, 2022)
Emotional intelligence (EI) refers to a set of skills related to emotions and emotionalinformation. Organizational scholars have paid close attention to EI, and research has clarifiedthe definition and illuminated its role in organizations. In this section, the researchers defineEI and describe the abilities that comprise it. The researcher compares two approaches tomeasuring EI performance-based and self-report and review the findings on how EI is relatedto work criteria, categorizing them using three overarching models’ validity generalization,situation-specific, and moderator models. This paper aims at presenting the reviews of theliterature on Role of Emotional Intelligence & Employee Performance. In this research paperthe existing literature on Role of Emotional Intelligence and Employee Performance inorganizations is being reviewed. The review will give a holistic understanding of the Role ofEmotional Intelligence and Employee Performance concept for future researchers and aid toidentify the research gap.